Effect of Septoplasty on the Heart Rate Variability in Patients With Nasal Septum Deviation. Issue 2 (March 2018) - Celiker, Metin; Cicek, Yuksel; Tezi, Suat; Ozgur, Abdulkadir; Polat, Hatice Beyazal; Dursun, Engin
Abstract : Background: Nasal septum deformities (NSD) are one of the most common causes of upper airway obstruction. Heart rate variability (HRV) is a physiologic parameter that is affected by the balance between the sympathetic and parasympathetic tonus. Objective: The aim of this study was to evaluate the effects of a septoplasty operation on HRV parameters as assessed by 24 hours ambulatory Holter recordings in patients with NSD. Methods: The prospective study involved 54 consecutive patients (16 women and 38 men) who underwent septoplasty due to a marked C- or S-shaped NSD. Twenty-four-hour Holter monitoring was performed to all patients pre- and 2 months postseptoplasty operation. For the HRV analyses, the definitions of evaluated parameters were made according to the Task Force of European Society of Cardiology and the North American Society of Pacing and Electrophysiology on HRV. Results: Low-frequency norm () (73 [68–86] versus 78 [70–81], P  = 0.039) values were significantly increased after septoplasty whereas changes in other parameters were not statistically significant. Conclusion: The authors' study showed that low-frequency norm values were significantly increased after septoplasty operation in patients with NSD which may be interpreted as a decreased sympathetic tone.